2008
DOI: 10.1177/0363546508326983
|View full text |Cite
|
Sign up to set email alerts
|

Eccentric Loading versus Eccentric Loading plus Shock-Wave Treatment for Midportion Achilles Tendinopathy

Abstract: At 4-month follow-up, eccentric loading alone was less effective when compared with a combination of eccentric loading and repetitive low-energy shock-wave treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
283
0
16

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 290 publications
(312 citation statements)
references
References 30 publications
5
283
0
16
Order By: Relevance
“…55 There is considerable variability in the way eccentric exercise are performed, and it is not currently known which protocol is most effective. 88 Studies have specifically shown a decrease in pain 108,110,121 and improved VISA-A scores, 108,110 with an eccentric training program for those with midportion Achilles tendinopathy. Although Silbernagel et al 121 found a significant decrease in pain at 1-year follow-up, performance with jumping and toe raising did not improve with the eccentric program when compared to a control group.…”
Section: Eccentric Loadingmentioning
confidence: 99%
See 1 more Smart Citation
“…55 There is considerable variability in the way eccentric exercise are performed, and it is not currently known which protocol is most effective. 88 Studies have specifically shown a decrease in pain 108,110,121 and improved VISA-A scores, 108,110 with an eccentric training program for those with midportion Achilles tendinopathy. Although Silbernagel et al 121 found a significant decrease in pain at 1-year follow-up, performance with jumping and toe raising did not improve with the eccentric program when compared to a control group.…”
Section: Eccentric Loadingmentioning
confidence: 99%
“…The eccentric program was found to be superior to low-energy shock wave treatment 110 ; however, extracorporeal shockwave therapy (ESWT) combined with the eccentric program was better than eccentric exercises alone. 108 Additional studies have also noted an eccentric training program for those with midportion Achilles tendinopathy to decrease pain, 5,31,56,77,111,117 improve function, 111 improve VISA-A scores, 25,75,120 and increase strength. 5 Concentric exercises do not seem to have the same effect as an eccentric program.…”
Section: Eccentric Loadingmentioning
confidence: 99%
“…Additionally, combination of eccentric training with ESWT was shown to be more beneficial when compared with eccentric training alone. In an RCT consisting of 68 patients with chronic Achilles tendinopathy and a history of failed management, Rompe et al 16,17 found that combining ESWT with eccentric training yielded significant improvements in pain and function at a 4-month follow-up in midportion Achilles tendinopathy and at 1 year in insertional Achilles tendinopathy. These results should encourage clinicians to administer ESWT as an adjunct to eccentric training.…”
Section: Shock Wave Therapymentioning
confidence: 99%
“…Esses resultados podem ser explicados pelo fato do EFE afetar principalmente a atividade metabólica dos fibroblastos com maior produção e deposição ordenada de fibras de colágeno do tipo 1 e redução do fluido intratendíneo o que facilita a remodelação tecidual, como resultado tem-se um tendão mais propicio a suportar e transferir cargas 29,50 .…”
Section: Conflitos De Interessesunclassified